2000
DOI: 10.1038/sj.onc.1204014
|View full text |Cite
|
Sign up to set email alerts
|

Grb2 downregulation leads to Akt inactivation in heregulin-stimulated and ErbB2-overexpressing breast cancer cells

Abstract: ErbB2 can be activated by its own overexpression or be transactivated by the heregulin polypeptide growth factor. Activation of ErbB2 leads to breast cancer cell proliferation, presumably by inducing the activation of extracellular signal-regulated kinases 1,2 (Erk1,2) and Akt. We have previously reported that the growth factor receptor bound protein-2 (Grb2) is required for the proliferation of ErbB2-overexpressing breast cancer cells. We investigated here whether Grb2 protein plays a role in heregulin-stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 44 publications
0
32
1
Order By: Relevance
“…We found that serum growth factors and Grb2 predominantly regulate Akt activity in Her2/neu-overexpressing cells, while serum growth factors and Grb2 predominantly regulate Erk1,2 activities in EGFR-overexpressing cells Lim et al, 2000). Other groups illustrated that it was the expression/ activation of Her2/neu, not EGFR, which promotes the retention of Raf-1 in the plasma membrane (Zhang et al, 2002), reinitiates the proliferation of growth-arrested mammary epithelial acini, and induces the luminal repopulation of mammary epithelial acini (Muthuswamy et al, 2001).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…We found that serum growth factors and Grb2 predominantly regulate Akt activity in Her2/neu-overexpressing cells, while serum growth factors and Grb2 predominantly regulate Erk1,2 activities in EGFR-overexpressing cells Lim et al, 2000). Other groups illustrated that it was the expression/ activation of Her2/neu, not EGFR, which promotes the retention of Raf-1 in the plasma membrane (Zhang et al, 2002), reinitiates the proliferation of growth-arrested mammary epithelial acini, and induces the luminal repopulation of mammary epithelial acini (Muthuswamy et al, 2001).…”
Section: Discussionmentioning
confidence: 90%
“…We have shown that Grb2 regulates Akt activity in heregulin-stimulated and Her2/neu overexpressing breast cancer cells (Lim et al, 2000). Increased Akt activity has been found in many types of cancer.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations